Forecasting Cardiovascular Drug Demand Using Triple Exponential Smoothing Additive - Chairun Wiedyaningsih; Endang Yuniarti; Andi Fadilla (GLOBAL HEALTH SCIENCE GROUP, 2025)
Drug management and pharmaceutical services in hospitals often face two main problems: stockouts and overstocking. This research aims to apply the Triple Exponential Smoothing (TES) additive method to forcast cardiovascular drug needs for the period of January–March 2024 at RSUD Dr. Kanujoso Djatiwibowo. This research employs a retrospective method using cardiovascular drugs data collected between January 2021 and December 2023. The forecasting results were interpreted using Mean Absolute Percentage Error (MAPE). The forecasting conducted in the range of January - March 2024, there four drug items distribute in highly accurate forecasts (MAPE<10%), while four drugs exhibited good forecasting performance (MAPE 10%-20%). Additionally, two drug items showed fair forecast results (MAPE 20%-50). This study concluded that RSUD Dr. Kanujoso Djatiwibowo could use TES Additive forecasting method.